Functional Group Distribution of the Carrier Surface Influences Adhesion of Methanothermobacter thermautotrophicus. (23rd January 2020) - Umetsu, Masaki; Sunouchi, Takaaki; Fukuda, Yasuhiro; Takahashi, Hideyuki; Tada, Chika
Abstract : Various support carriers are used for high-density retention of methanogenic archaea in anaerobic wastewater treatment systems. Although the physicochemical properties of carrier materials and microorganisms influence the adhesion of methanogenic archaea, details about the underlying mechanism remain poorly characterized. We applied seven types of chemical surface modifications to carbon felts to clarify the adhesion properties of Methanothermobacter thermautotrophicus, a representative thermophilic hydrogenotrophic methanogen. The relationship between carrier surface properties and methanogen adhesion was evaluated. M. thermautotrophicus adhesion was significantly increased up to 2.6 times in comparison with control on carbon felts treated with NaOH, HCl, H2 SO4, or Na2 HPO4 . Treated carbon felts showed a lower water contact angle, but no correlation between the carrier surface contact angle and methanogen adhesion was observed. On the other hand, at the surface of the carrier that showed improved adhesion of methanogens, the ratio of -COOH : -OH was 1 : 0.65. Such a ratio was not observed with treated carriers for which methanogen adhesion was not improved. Therefore, in the adhesion of M. thermautotrophicus, the functional group abundance was important as well as physical surface properties such as the hydrophobicity. Hydrogenotrophic methanogens are involved in active methanation during the startup of anaerobic digestion. Additionally, these methanogenic archaea function as methanogenic cathode catalysts. Therefore, anaerobic digestion performance will greatly improve by controlling the adhesion of hydrogenotrophic methanogens such as M. thermautotrophicus .